The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.scr.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Generation of functional podocytes from human induced pluripotent stem cells

Abstract: Generating human podocytes in vitro could offer a unique opportunity to study human diseases. Here, we describe a simple and efficient protocol for obtaining functional podocytes in vitro from human induced pluripotent stem cells. Cells were exposed to a three-step protocol, which induced their differentiation into intermediate mesoderm, then into nephron progenitors and, finally, into mature podocytes. After differentiation, cells expressed the main podocyte markers, such as synaptopodin, WT1, α-Actinin-4, P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 39 publications
1
69
0
Order By: Relevance
“…In an effort to generate tools for both drug discovery and drug safety within the area of kidney disease, we aimed to develop an in vitro model for glomerular health using hiPSCs. To date, some recent progress has been made toward this end, [1][2][3][4][5]28 but there are still no established functional tools mimicking the human situation in the screening format required for drug discovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to generate tools for both drug discovery and drug safety within the area of kidney disease, we aimed to develop an in vitro model for glomerular health using hiPSCs. To date, some recent progress has been made toward this end, [1][2][3][4][5]28 but there are still no established functional tools mimicking the human situation in the screening format required for drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…The induced pluripotent stem cell (iPSC) technology has made it possible to access and modify cells of a wide variety of origins that previously have been difficult or nearly impossible to study. Within the field of nephrology, some recent advances have been made in creating 3-dimensional (3D) organoid cultures, [1][2][3][4][5] but there are still limited functional tools for drug discovery available.…”
mentioning
confidence: 99%
“…Urinary renal progenitor cells have the potential to be used as a non-invasive source for studying personalized genetic kidney disease, but the number of progenitor cells present in urine varies and hampers the success rate of urine-derived progenitor and associated podocyte cultures. To overcome this hurdle, the use of (patient-derived) induced pluripotent stem cells (iPSC) and differentiation towards podocytes is a promising approach [21][22][23][24]. Tanigawa and co-workers successfully reprogrammed skin fibroblasts isolated from a newborn diagnosed with congenital NS into iPSC [12].…”
Section: Functional Assessment Of Genetic Variantsmentioning
confidence: 99%
“…2). Using either 2D or 3D culture approaches, and varying the choice and/or timing of growth factors, result in the induction of one renal cell type (e.g., podocyte-like cells) [15,21,55,56] or in self-organizing kidney organoids consisting of segmented nephrons [22,23,[57][58][59]. These protocols are extensively reviewed by Soo et al [60].…”
Section: Modeling Ns Using Stem Cellsmentioning
confidence: 99%
“…Currently, there are several studies that have reported the differentiation of hPSCs into cells of the kidney lineage [37, 34, 35, 64]. Kidneys consist of many different cell types in the nephron, vasculature and interstitial compartments.…”
Section: Comparison Of Kidney Organoid Differentiation Protocolsmentioning
confidence: 99%